Population and Characterization of Rhyzospheric Bacteria of Pineapple Plant (Ananas comosus L. Merr) on The Highland Land of Lumban Sihite Village, Regency Dairi - Ginting, Monika; Manalu, Kartika; Nasution, Rizki Amelia (Jurnal Biologi Tropis, 2024)
The rhizosphere is the part of the soil around the roots of plants which is known to have a greater number of rhizosphere bacteria compared to the soil far from the roots. This research aims to determine the population and characteristics of rhizosphere bacteria from pineapple plants (Ananas comosus L. Merr) on the highland land of Lumban Sihite village, Dairi district. The stages used in this research were taking samples at three different points, then carrying out multilevel dilutions, inoculating them into petri dishes filled with PCA (Plate Count Agar) media, then counting the growing colonies using the TPC (total plate count) method, purification, morphological characterization, gram staining and biochemical tests. The research results obtained at point 3 had the largest population of 463.96 x 10⁴ CFU/g, while point 1 had the lowest population, namely 20.07 x 10⁴ CFU/g. Based on the results of morphological, gram staining and biochemical characterization of bacterial isolates, the isolates were identified as belonging to the genus Azospirillum, Bacillus, Pseudomonas and Azotobacter.